Distribution of functional groups in periodic mesoporous organosilica materials studied by small-angle neutron scattering with in situ adsorption of nitrogen - Sharifi, Monir; Wallacher, Dirk; Wark, Michael (Beilstein Journal of Nanotechnology, 2012)
Periodic mesoporous materials of the type (R′O)3Si-R-Si(OR′)3 with benzene as an organic bridge and a crystal-like periodicity within the pore walls were functionalized with SO3H or SO3− groups and investigated by small-angle neutron scattering (SANS) with in situ nitrogen adsorption at 77 K. If N2 is adsorbed in the pores the SANS measurements show a complete matching of all of the diffraction signals that are caused by the long-range ordering of the mesopores in the benzene-PMO, due to the fact that the benzene-PMO walls possess a neutron scattering length density (SLD) similar to that of nitrogen in the condensed state. However, signals at higher q-values (>1 1/Å) are not affected with respect to their SANS intensity, even after complete pore filling, confirming the assumption of a crystal-like periodicity within the PMO material walls due to π–π interactions between the organic bridges. The SLD of pristine benzene-PMO was altered by functionalizing the surface with different amounts of SO3H-groups, using the grafting method. For a low degree of functionalization (0.81 mmol SO3H·g−1) and/or an inhomogeneous distribution of the SO3H-groups, the SLD changes only negligibly, and thus, complete contrast matching is still found. However, for higher amounts of SO3H-groups (1.65 mmol SO3H·g−1) being present in the mesopores, complete matching of the neutron diffraction signals is no longer observed proving that homogeneously distributed SO3H-groups on the inner pore walls of the benzene-PMO alter the SLD in a way that it no longer fits to the SLD of the condensed N2.
Keywords: contrast matching; crystal-like periodicity; distribution of functional groups; PMO; SANS; surface functionalization

(untitled) - Taguchi, A.; Schüth, F. (Microporous Mesoporous Mater., 2005)

(untitled) - Jones, C. W.; Tsuji, K.; Davis, M. E. (Nature, 1998)

(untitled) - Hoffmann, F.; Cornelius, M.; Morell, J.; Fröba, M. (Angew. Chem., Int. Ed., 2006)

(untitled) - Gartmann, N.; Brühwiler, D. (Angew. Chem., Int. Ed., 2009)

(untitled) - Inagaki, S.; Guan, S.; Fukushima, Y.; Ohsuna, T.; Terasaki, O. (J. Am. Chem. Soc., 1999)

(untitled) - Melde, B. J.; Holland, B. T.; Blanford, C. F.; Stein, A. (Chem. Mater., 1999)

(untitled) - Asefa, T.; MacLachlan, M. J.; Coombs, N.; Ozin, G. A. (Nature, 1999)

(untitled) - Fujita, S.; Inagaki, S. (Chem. Mater., 2008)

(untitled) - de A. A. Soler-Illia, G. J.; Sanchez, C.; Lebeau, B.; Patarin, J. (Chem. Rev., 2002)

(untitled) - Bion, N.; Ferreira, P.; Valente, A.; Gonçalves, I. S.; Rocha, J. (J. Mater. Chem., 2003)

(untitled) - Nakajima, K.; Tomita, I.; Hara, M.; Hayashi, S.; Domen, K.; Kondo, J. N. (Catal. Today, 2006)

(untitled) - Boury, B.; Corriu, R. J. P.; Le Strat, V.; Delord, P.; Nobili, M. (Angew. Chem., Int. Ed., 1999)

(untitled) - Boury, B.; Ben, F.; Corriu, R. J. P.; Delord, P.; Nobili, M. (Chem. Mater., 2002)

(untitled) - Kruk, M.; Jaroniec, M.; Sayari, A. (Langmuir, 1997)

(untitled) - Kumar, D.; Schumacher, K.; Du Fresne von Hohenesche, C.; Grün, M.; Unger, K. K. (Colloids Surf., A, 2001)

(untitled) - Zhang, J.; Zhang, Q.; Li, X.; Liu, S.; Ma, Y.; Shi, F.; Deng, Y. (Phys. Chem. Chem. Phys., 2010)

(untitled) - Rückriem, M.; Inayat, A.; Enke, D.; Gläser, R.; Einicke, W.-D.; Rockmann, R. (Colloids Surf., A, 2010)

(untitled) - Morell, J.; Teixeira, C. V.; Cornelius, M.; Rebbin, V.; Tiemann, M.; Amenitsch, H.; Fröba, M.; Lindén, M. (Chem. Mater., 2004)

(untitled) - Tun, Z.; Mason, P. C.; Mansour, F. K.; Peemoeller, H. (Langmuir, 2002)

(untitled) - Bragg, W. L.; Perutz, M. F. (Acta Crystallogr., 1952)

(untitled) - Ramsay, J. D. F.; Wing, G. (J. Colloid Interface Sci., 1991)

(untitled) - Smarsly, B.; Thommes, M.; Ravikovitch, P. I.; Neimark, A. V. (Adsorption, 2005)

(untitled) - Smarsly, B.; Göltner, C.; Antonietti, M.; Ruland, W.; Hoinkis, E. (J. Phys. Chem. B, 2001)

(untitled) - Sel, O.; Brandt, A.; Wallacher, D.; Thommes, M.; Smarsly, B. (Langmuir, 2007)

(untitled) - Sharifi, M.; Marschall, R.; Wilhelm, M.; Wallacher, D.; Wark, M. (Langmuir, 2011)

(untitled) - Mascotto, S.; Wallacher, D.; Kuschel, A.; Polarz, S.; Zickler, G. A.; Timmann, A.; Smarsly, B. M. (Langmuir, 2010)

(untitled) - Sharifi, M.; Köhler, C.; Tölle, P.; Frauenheim, T.; Wark, M. (Small, 2011)

(untitled) - Wilhelm, M.; Jeske, M.; Marschall, R.; Cavalcanti, W. L.; Tölle, P.; Köhler, C.; Koch, D.; Frauenheim, T.; Grathwohl, G.; Caro, J.; Wark, M. (J. Membr. Sci., 2008)

(untitled) - Choi, Y.; Kim, Y.; Kim, H. K.; Lee, J. S. (J. Membr. Sci., 2010)

(untitled) - Klaysom, C.; Marschall, R.; Wang, L.; Ladewig, B. P.; Lu, G. Q. M. (J. Mater. Chem., 2010)

(untitled) - Seger, B.; Kamat, P. V. (J. Phys. Chem. C, 2009)

(untitled) - Marschall, R.; Klaysom, C.; Mukherji, A.; Wark, M.; Lu, G. Q. M.; Wang, L. (Int. J. Hydrogen Energy, 2012)

(untitled) - Zhao, X. S.; Lu, G. Q. (J. Phys. Chem. B, 1998)

(untitled) - El-Merraoui, M.; Aoshima, M.; Kaneko, K. (Langmuir, 2000)

(untitled) - Brühwiler, D. (Nanoscale, 2010)

(untitled) - Li, J. C.; Ross, D. K.; Howe, L. D.; Stefanopoulos, K. L.; Fairclough, J. P. A.; Heenan, R.; Ibel, K. (Phys. Rev. B, 1994)

(untitled) - Ramsay, J. D. F.; Kallus, S. (J. Non-Cryst. Solids, 2001)

Die Porenstruktur von Kohlen - Prinz, D. (Rheinisch-Westfälische Technische Hochschule, 2004)

(untitled) - Bellissent, R.; Descotes, L.; Boué, F.; Pfeuty, P. (Phys. Rev. B, 1990)